2019
DOI: 10.1002/pc.25384
|View full text |Cite
|
Sign up to set email alerts
|

A novel strategy to reinforce glass fiber fabric/epoxy composites via modifying fibers with self‐assembled multi‐walled carbon nanotubes‐montmorillonite

Abstract: A novel strategy of multi‐walled carbon nanotubes‐montmorillonite (MWCNTs‐Mt)‐modified glass fiber fabrics (GFf) was used here to reinforce interlaminar regions of epoxy composites. One/two‐dimensional MWCNTs‐Mt hybrids with different mass ratios of MWCNTs and Mt were combined with the GFf, respectively, prior to a resin injection process. Making use of this strategy, uniformly dispersed MWCNTs and highly exfoliated Mt at the fiber/matrix interface could be achieved; meanwhile, mechanical and interfacial prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…What volume fraction of CNTs to introduce into FRPs is often the first consideration for the design of CNT modified FRPs. [ 53–97 ] Halpin‐Tsai equations have often been used to calculate the Young's modulus of polymer composites reinforced by high aspect‐ratio particles. The detailed relationship is shown in Equation S1, Supporting Information.…”
Section: Mechanical Properties Of Cnt‐frps: Experimental Observationsmentioning
confidence: 99%
“…What volume fraction of CNTs to introduce into FRPs is often the first consideration for the design of CNT modified FRPs. [ 53–97 ] Halpin‐Tsai equations have often been used to calculate the Young's modulus of polymer composites reinforced by high aspect‐ratio particles. The detailed relationship is shown in Equation S1, Supporting Information.…”
Section: Mechanical Properties Of Cnt‐frps: Experimental Observationsmentioning
confidence: 99%
“…It is assumed that the damping of the GF at ambient temperature is negligible and energy dissipation in GF/epoxy composites is attributed to the matrix and fiber/matrix interactions at the interface. Based on the damping of epoxy matrix and composites, the interfacial interaction factors, a and A, have been given and can be calculated by equation (1) 25,26 and equation ( 2), [27][28][29] respectively. Both high a value and low A value indicate strong interfacial adhesion.…”
Section: Measurements and Characterizationmentioning
confidence: 99%
“…[ 21 ] The modified glass fiber (GF) fabric/epoxy composites with multi‐walled carbon nanotube and montmorillonite fillers increased the interlaminar shear strength significantly comparing to the unfilled composites. [ 22 ] Wan Ramli et al reported that the interfacial bonding between the fiber and the matrix was complemented by adding 5 wt% of NC in Napier fiber‐reinforced epoxy composites. [ 23 ]…”
Section: Introductionmentioning
confidence: 99%